2016
DOI: 10.3920/jiff2015.0089
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on alternative substrate for multiplication of African palm weevil under captive management

Abstract: The dearth of animal protein in Nigeria and the need for environmental friendly animal protein productionnecessitates the use of edible insects as an alternative protein source. To ensure the sustainability of edible insects, a cost-effective captive method of rearing needs to be devised. This study was designed to investigate alternative culture media for rearing African palm weevil Rhynchophorus phoenicis under captive management. One hundred and sixty eight palm weevils collected from ‘Mgbo swamp’ in Ebeneb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…First, insects themselves carry and disperse a guild of appropriate microorganisms helping them to establish an insect-favorable habitat. Phytophagous [ 233 ] and sarcosaphrophagous Diptera [ 234 ] often use their bacteria to digest their feed. Mouthparts and gross maggot morphology are specialized purposely for the job, even in the less specialized Hermetia [ 235 ].…”
Section: Insects As Sources Of Dietary Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, insects themselves carry and disperse a guild of appropriate microorganisms helping them to establish an insect-favorable habitat. Phytophagous [ 233 ] and sarcosaphrophagous Diptera [ 234 ] often use their bacteria to digest their feed. Mouthparts and gross maggot morphology are specialized purposely for the job, even in the less specialized Hermetia [ 235 ].…”
Section: Insects As Sources Of Dietary Proteinsmentioning
confidence: 99%
“…Bacteria have a different exciting role in recycling byproducts associated with insect rearing [ 237 ]. In captive mass breeding of well-accepted Palm Weevil grubs [ 233 ], bacteria play a relevant part in pre-digesting the artificial diet matter. A further argument about food insect association with microorganisms consists in fermenting bacteria associated with processed, stored, and traded food insects [ 243 ].…”
Section: Insects As Sources Of Dietary Proteinsmentioning
confidence: 99%
“…Other common species are palm weevils larvae and beetles, such as Rhynchophorus ferrugineus, while Rhynchophorus palmarum is more common in Latin America. Palm weevil larvae and beetles (Rhynchophorus phoenicis) are highly appreciated throughout Africa, and can be reared on cheap substrates (Ebenebe and Okpoko 2016) A summary on the extent of entomophagy in 15 Asian countries is summarised in Table 8, which indicates the production mode and utilisation. Wild harvesting is still very widespread among the countries for both subsistence and commercial purposes, even though farming is more likely to boost commercialisation (Yen 2015).…”
Section: Asiamentioning
confidence: 99%
“…These systems of farming represent 30 to 75% of the household income in the study area. (Ebenebe & Okpoko, 2016) reported 8 different culturing substrates for rearing Palm weevil (coconut fiber, coconut fiber with palm wine, sawdust of mahogany, sawdust of mahogany with palm wine, palm frond petiole, palm bunch midrib, sugarcane tops (SCT), spoilt watermelon (SWM)). The result revealed that the larva thrived better in spoilt water melon and sugarcane top but failed to pupate in SWM.…”
Section: Entrepreneurial Potentials Of Farming Insects For Foodmentioning
confidence: 99%